Emerging rodent-associated Bartonella: a threat for human health? - Maria Krügel; Nina Król; Volkhard A. J. Kempf; Martin Pfeffer; Anna Obiegala (Parasites & Vectors, 2022)
Abstract Background Species of the genus Bartonella are facultative intracellular alphaproteobacteria with zoonotic potential. Bartonella infections in humans range from mild with unspecific symptoms to life threatening, and can be transmitted via arthropod vectors or through direct contact with infected hosts, although the latter mode of transmission is rare. Among the small mammals that harbour Bartonella spp., rodents are the most speciose group and harbour the highest diversity of these parasites. Human–rodent interactions are not unlikely as many rodent species live in proximity to humans. However, a surprisingly low number of clinical cases of bartonellosis related to rodent-associated Bartonella spp. have thus far been recorded in humans. Methods The main purpose of this review is to determine explanatory factors for this unexpected finding, by taking a closer look at published clinical cases of bartonellosis connected with rodent-associated Bartonella species, some of which have been newly described in recent years. Thus, another focus of this review are these recently proposed species. Conclusions Worldwide, only 24 cases of bartonellosis caused by rodent-associated bartonellae have been reported in humans. Possible reasons for this low number of cases in comparison to the high prevalences of Bartonella in small mammal species are (i) a lack of awareness amongst physicians of Bartonella infections in humans in general, and especially those caused by rodent-associated bartonellae; and (ii) a frequent lack of the sophisticated equipment required for the confirmation of Bartonella infections in laboratories that undertake routine diagnostic testing. As regards recently described Bartonella spp., there are presently 14 rodent-associated Candidatus taxa. In contrast to species which have been taxonomically classified, there is no official process for the review of proposed Candidatus species and their names before they are published. This had led to the use of malformed names that are not based on the International Code of Nomenclature of Prokaryotes. Researchers are thus encouraged to propose Candidatus names to the International Committee on Systematics of Prokaryotes for approval before publishing them, and only to propose new species of Bartonella when the relevant datasets allow them to be clearly differentiated from known species and subspecies. Graphical Abstract